A Companion to Experimental Philosophy 2016
DOI: 10.1002/9781118661666.ch36
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Philosophical Logic

Abstract: The purpose of this chapter is to explore the intersection of experimental philosophy and philosophical logic, an intersection I'll call experimental philosophical logic. In particular, I'll be looldng for and sketching some ways in which experimental results, and empirical results more broadly, can inform and have informed debates within philosophical logic. Here's the plan: first, I'll lay out a way of looking at the situation that makes plain at least one way in which we should expect experimental and logic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Research works in logic fall under two broad categories (Ripley 2016;Priest 2005). 6 There are works in pure logic and there are works in applied logic.…”
Section: Pure and Applied Logicmentioning
confidence: 99%
See 3 more Smart Citations
“…Research works in logic fall under two broad categories (Ripley 2016;Priest 2005). 6 There are works in pure logic and there are works in applied logic.…”
Section: Pure and Applied Logicmentioning
confidence: 99%
“…The reasoners could just be employing some other system of logic. For example, data from the Wason card-selection experiment have shown that human reasoners are poor at judging conditional statements (Ripley 2016;Joaquin and Agregado 2018). But from these data, Cohen argues, we could not make any evaluation of the adequacy of the implied normative, classical logical system assumed in the experiments since such a logical framework is just assumed by the experimenters.…”
Section: Experimental Data and Philosophical Logicmentioning
confidence: 99%
See 2 more Smart Citations